Cross-Modality Continuous User Authentication and Device Pairing With Respiratory Patterns - Islam, Shekh M. M.; Zheng, Yao; Pan, Yanjun; Millan, Marionne; Chang, Willy; Li, Ming; Boric-Lubecke, Olga; Lubecke, Victor; Sun, Wenhai (IEEE internet of things journal, 2023)
At-home screening systems for obstructive sleep apnea (OSA) can bring convenience to remote chronic disease management. However, the unsupervised home environment is subject to spoofing and unintentional interference from the household member. To improve robustness, this work presents SIENNA, an insider-resistant breathing-based authentication/pairing protocol. SIENNA leverages the uniqueness of breathing patterns to automatically and continuously authenticate a user and pairs a mobile OSA app and a physiological monitoring radar system (PRMS). SIENNA does not require biometric enrollment and instead transforms the respiratory measurements taken during the user's routine physical checkup into breathing biometrics comparable with the PRMS readings. Furthermore, it can operate within a noisy multitarget home environment and is secure against a co-located attacker through the usage of joint approximate diagonalization of eignematric-independent component analysis, fuzzy commitment, and friendly jamming. We fully implemented SIENNA and evaluated its performance with medium-scale trials. Results show that SIENNA can achieve reliable (>90 % success rate) user authentication and secure device pairing in a noisy environment against an attacker with full knowledge of the authorized user's breathing biometrics.